Hadis Sebagai Sumber Rujukan dan Ambilan Hukum bagi Jawatankuasa Fatwa Negeri Perlis: Kedudukan dan Aplikasi: Hadis as a Source of Reference and Hukum for State Fatwa Committee of Perlis: Status and Application - Azid, Muhammad Adam Abd.; Ahmad, Khadher; Md Ariffin, Mohd Farhan; Dahaman @ Dahlan, Mohd Akram (Maʿālim al-Qurʾān wa al-Sunnah, 2019)
State Fatwa Committee of Perlis is one of fatwa (formal ruling) institutions in Malaysia. The committe is responsible in issuing any fatwa relating to Islamic affairs in Perlis. State Fatwa Committee of Perlis has its own speciality in terms of reference and source in issuing any fatwa. The Quran and hadith are made as the foundational sources in issuing fatwa compared to madhhabi approach practiced by another fatwa institution in Malaysia. This is based on the provision under Section 54 (1) of Perlis Islamic Administration Enactment 2006, which stated that the Quran and Hadis as the main sources in issuing fatwa by State Fatwa Committee of Perlis. A similar fatwa entitled “Keputusan Fatwa Mengenai Ahli Sunnah Wa al-jama’ah” (Issuance Fatwa related to Ahli Sunnah Wal Jamaah)” issued by State Fatwa Committee of Perlis also recognized hadith as the main reference and source to Perlis Fatwa Department. However, there is no detail explanation in the enactment as well as the above fatwa about the meaning of hadith and its application by State Fatwa Committee of Perlis. This study has been carried out in order to observe the interpretation of the ṣaḥīḥ, mursal and ḍa’īf hadith based on the State Fatwa Committee of Perlis’s perspective and practice. This study also highlights the method used by the State Fatwa Committee of Perlis in applying the hadith in issuance of a fatwa. In collecting data, this qualitative study employs the method of literature review and interview. To summarize the study, three types of hadith namely ṣaḥīḥ (including ḥasan), mursal and ḍa’īf were applied by State Fatwa Committee of Perlis. While the application of a hadith in the fatwa issuance process, the committee try to apply literal meaning of hadith ahead of other methods of interpretation.